Muscle diseases: mimics and chameleons. Issue 5 (13th June 2014) - Walters, R Jon
Abstract : Muscle diseases are not as common as headaches and funny turns in our general neurology clinics, but most of us will encounter them. We all pride ourselves on a methodical approach to clinical problems—discovering the where and what in neurological parlance—but any diagnostic process can unravel, particularly if one condition resembles another. Before we settle on a diagnosis, we need to ask ourselves, whether the 'ducks all line up' to avoid cases of mistaken identity.